PECULIARITIES OF TEACHING LATIN TO FUTURE PHILOLOGISTS - Ruslan M. Kliuchnyk; Larysa V. Ratomska (Alfred Nobel University Publisher, 2022)
The article considers some aspects of teaching the Latin language to future philologists. Special attention has been paid to the historical aspect of teaching Latin. The differences between teaching Latin and teaching modern languages have been distinguished. It has been stressed that Ukrainian students do not need to obtain all language competencies while learning this course. Among them are philologists, Law students, medical students, etc. The authors pay special attention to training philologists as they are likely to teach the basics of Latin to the students of other majors. There are some problems connected with the study of Latin in the 21st century. For instance, this language is learnt only for one or two semesters in modern Ukrainian institutions of higher education. Therefore, it is impossible to learn a large number of Latin words. So, the authors recommend choosing some frequently used words, as well as some proper nouns. It has been underlined that learning Latin is a complicated activity because of the absence of native speakers and lack of definitive knowledge about the Latin phonetics. It has been mentioned that not so many texts survive from Classical Antiquity and there is only a limited number of post-classical Latin-language texts. This language, like any other one, has changed a lot, so we focus on learning Classical Latin. It was used as a literary standard by writers of the late Roman Republic and early Roman Empire. But we use the texts adapted for the present-day students. Foe example, the words are spelt separately and the letters u and j are used. In this article the authors have distinguished several clusters of Latin words that are to be learnt. Students are asked to find out the etymology of modern English words that have Latin origin. It has been shown that Latin helps students to get ready for learning other languages. The linguodidactic potential of Latin proverbs has been shown. Besides, the authors have used some mottos of countries, regions and cities. It is suggested to use modern Internet sources including Englishlanguage ones. The article contains an example of a multiple-choice exercise aimed at training grammar skills. The authors assume that learning Latin should be supported with discussions and self-study work presentations. Special attention is paid to motivation of students.